Pertanggungjawaban Rumah Sakit J.K. Atas Kelalaian Dalam Pelayanan Kesehatan Terhadap Pasien Ditinjau Dari Undang-Undang Nomor 44 Tahun 2009 Tentang Rumah Sakit - Kurniawan Sinambung Agung (Darma Cendika Catholic University, 2019)
The health law is all regulations directly related to health care and the application on civil law, administrative law, or criminal law. In order to achieve successful health development, it is important to achieve harmony between the interests of the patient and the interests of the medical staffs. Furthermore, hospitals as the health administrator must also fulfil their tasks and functions to achieve high quality health care or duty of care, giving a good and reasonable service. The patient’s rights are regulated in Article 32 Law Number 44 Year 2009 on Hospitals. Should there be patients harmed due to negligence of the medical staff, the hospital will be held responsible. The image that hospitals are above the law is no longer valid. Hospitals’ accountability in Indonesia is regulated in Article 46 Law Number 44 Year 2009 on Hospitals. In order to decide the accountability of a hospital, it is necessary to see the therapeutic relation between the hospital-patient or doctor-patient.